2015
DOI: 10.3748/wjg.v21.i26.8110
|View full text |Cite
|
Sign up to set email alerts
|

Effect of technical parameters on transjugular intrahepatic portosystemic shunts utilizing stent grafts

Abstract: TIPS stent-to-caval distance and other parameters have no significant effect on primary patency, time to recurrence of symptoms, or all-cause mortality following TIPS with a stent-graft.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
2
5
0
Order By: Relevance
“…Our study found no relation between TIPS angulation and shunt revision rate or overall survey. This result is in accordance with other series, either with bare metal stents (19)(20)(21) or with graft stents as well (23). It is well-known that covered stents (Viatorr ® stent or bare-metal stent + covered stent) give better outcomes and long-term shunt patency than uncovered bare metal stents alone, with no difference between dedicated Viatorr ® stent and other covered stents (31).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our study found no relation between TIPS angulation and shunt revision rate or overall survey. This result is in accordance with other series, either with bare metal stents (19)(20)(21) or with graft stents as well (23). It is well-known that covered stents (Viatorr ® stent or bare-metal stent + covered stent) give better outcomes and long-term shunt patency than uncovered bare metal stents alone, with no difference between dedicated Viatorr ® stent and other covered stents (31).…”
Section: Discussionsupporting
confidence: 91%
“…The use of graft stents seems to be associated with lower intimal hyperplasia (36,37). The combination of those two factors probably explains why position of the vein end graft stent and then the distance between stent and inferior vena cava had no influence on the shunt patency in our study as in the study by Andring et al (23). It suggests that positioning of the end vein graft stent at the junction of the ICV with SHV should not be a priority during TIPS procedure.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Andring et al[ 15 ] have suggested that whether the end of the stent position in relation to the hepatic vein IVC confluence or other factors of tract angle, such as portal vein to parenchymal tract and hepatic vein to parenchymal tract, have little effect on the primary patency rate, which leads to recurrence of symptoms and related mortality following TIPS.…”
Section: Discussionmentioning
confidence: 99%
“…The dilemma of initial stent position during TIPS placement can have several clinical implications[ 22 ]. Andring et al[ 15 ] have shown that the hepatic venous end of TIPS stent graft position in relation to the hepatic vein and IVC junction has little effect on the primary patency rate following TIPS. Similarly, other factors such as whether access to the portal vein of the stent involved the inflow end also has no significant effect on primary patency, which leads to recurrence of symptoms and TIPS-related mortality.…”
Section: Discussionmentioning
confidence: 99%